2016
DOI: 10.1128/jb.00784-15
|View full text |Cite
|
Sign up to set email alerts
|

σ Factor and Anti-σ Factor That Control Swarming Motility and Biofilm Formation in Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is capable of causing a variety of acute and chronic infections. Here, we provide evidence that sbrR (PA2895), a gene previously identified as required during chronic P. aeruginosa respiratory infection, encodes an anti-factor that inhibits the activity of its cognate extracytoplasmic-function factor, SbrI (PA2896). Bacterial two-hybrid analysis identified an N-terminal region of SbrR that interacts directly with SbrI and that was sufficient for inhibition of SbrI-dependent gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 60 publications
3
26
0
1
Order By: Relevance
“…The differential proteomics data confirmed proteins known to play a role in biofilm formation and growth. These included MuiA, which inhibited swarming motility and enhanced biofilm formation (roles, that were validated in knockout strains) [40], and CbpD, for which higher protein expression had been observed in late phases of biofilm growth; accordingly, mutants displayed a lower amount of biofilm growth and exopolysaccharides (EPS) [41]. Inactivation studies showed that the gene encoding AcnA impaired biofilm formation and was required for microcolony formation [42], while increased expression of PilY1 repressed swarming and increased biofilm formation, as confirmed by knockout experiments [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The differential proteomics data confirmed proteins known to play a role in biofilm formation and growth. These included MuiA, which inhibited swarming motility and enhanced biofilm formation (roles, that were validated in knockout strains) [40], and CbpD, for which higher protein expression had been observed in late phases of biofilm growth; accordingly, mutants displayed a lower amount of biofilm growth and exopolysaccharides (EPS) [41]. Inactivation studies showed that the gene encoding AcnA impaired biofilm formation and was required for microcolony formation [42], while increased expression of PilY1 repressed swarming and increased biofilm formation, as confirmed by knockout experiments [43].…”
Section: Discussionmentioning
confidence: 99%
“…Among the most significantly differentially expressed proteins (log 2 fold change (FC) of ≥ 1 or ≤ -1 and adjusted p value ≤ 0.05; see Methods) several candidates were identified that have previously been linked with a role in biofilm formation. These included MuiA (MPAO1_18330) [40], CbpD (MPAO1_21730) [41], AcnA (MPAO1_17965) [42] and PilY1 (MPAO1_24155) [43] (Fig. 5a, Table 3; see Discussion).…”
Section: Protein Expression Profiling Of Mpao1 Grown Planktonic and Imentioning
confidence: 99%
See 1 more Smart Citation
“…An σ ECF factor belonging to the ECF35 group, which is specific for Proteobacteria (Staroń et al , ), has been recently characterized in P. aeruginosa and named σ SbrI for swarming‐ and biofilm‐related due to its regulatory role in swarming motility and biofilm formation (McGuffie et al , ). DIAMOND BLASTp analyses shows that homologues to σ SbrI are present in P. protegens and P. fluorescens but not in P. putida and P. syringae (Dataset and Table ).…”
Section: Stress‐responsive Pseudomonas σEcf Factorsmentioning
confidence: 99%
“…Likewise, sbrR is a factor involved in swimming ability [33], and would hence had been expected to be involved in the resistance to cephalosporins such as Ceftazidime, not the aminoglycoside Gentamicin (Table 3).…”
Section: High Sensitivity Of Rrf With Chunkingmentioning
confidence: 99%